The Effect of Liver Transplantation on Anti‐Glycaemic Agents in Patients With Pre‐Existing Diabetes Mellitus: A Population‐Based Cohort Study - Amy Coulden; Christina Antza; Orighomisan Awala; Nihit Shah; Leelavathy Kandaswamy; Ananda Nahar; Angela Phillips; Sneha Upadhyaya; Ayesha Asif; Zara Khan; Feaz Babwah; Matthew Armstrong; et al. (Journal of Diabetes, 2025)
ABSTRACT Background Anecdotally, patients with diabetes mellitus after undertaking a liver transplant have reported improved glycaemic control and reduced insulin requirements, compared to other organ transplants where glycaemic control often worsens. This study aimed to evaluate possible changes in anti‐glycaemic agent requirements pre‐ and post‐liver transplantation and correlate them with the immunosuppression used and the reason for transplant. Methods In this observational, retrospective study, we investigated 258 adults with pre‐existing diabetes mellitus who underwent liver transplant from October 2009 to January 2020 at a tertiary UK center. We compared pre‐ and post‐transplant insulin treatment requirements. Results The mean age was 56 years, and the median duration of diabetes was 96 months. From a subgroup of 100 patients (38.8%) using insulin therapy, there was a reduction in insulin requirements from 60.5 ± 44.6 units/day before transplant to 51.1 ± 31.2 units/day at 1 month post‐transplantation (15.5%, p = 0.02), 43.4 ± 29.5 units/day at 3 months post‐transplantation (28.2%, p < 0.0001) and 33.6 ± 29.7 units/day at 6 months post‐transplantation (44.4%, p < 0.0001). There was a significant correlation between the difference in insulin requirement before and 6 months post‐transplant and the tacrolimus dose used as immunosuppressive therapy post‐liver transplant. There was no correlation with the use of other immunosuppressive therapies and change in insulin requirement. Conclusions Insulin requirements significantly reduced post‐liver transplant by almost 50%, despite initiation of immunosuppressive therapy. This is one of the first studies showing this effect, highlighting the role of the liver in regulating glucose metabolism, insulin utilization, and insulin resistance. Pooled data from other specialist centers need to be examined.